Potential of Sodium MRI as a Biomarker for Neurodegeneration and Neuroinflammation in Multiple Sclerosis - Huhn, Konstantin; Engelhorn, Tobias; Linker, Ralf A.; Nagel, Armin M. (Frontiers in Neurology, 2019)
In multiple sclerosis (MS), experimental and ex vivo studies indicate that pathologic intra- and extracellular sodium accumulation may play a pivotal role in inflammatory as well as neurodegenerative processes. Yet, in vivo assessment of sodium in the microenvironment is hard to achieve. Here, sodium magnetic resonance imaging (23NaMRI) with its non-invasive properties offers a unique opportunity to further elucidate the effects of sodium disequilibrium in MS pathology in vivo in addition to regular proton based MRI. However, unfavorable physical properties and low in vivo concentrations of sodium ions resulting in low signal-to-noise-ratio (SNR) as well as low spatial resolution resulting in partial volume effects limited the application of 23NaMRI. With the recent advent of high-field MRI scanners and more sophisticated sodium MRI acquisition techniques enabling better resolution and higher SNR, 23NaMRI revived. These studies revealed pathologic total sodium concentrations in MS brains now even allowing for the (partial) differentiation of intra- and extracellular sodium accumulation. Within this review we (1) demonstrate the physical basis and imaging techniques of 23NaMRI and (2) analyze the present and future clinical application of 23NaMRI focusing on the field of MS thus highlighting its potential as biomarker for neuroinflammation and -degeneration.